2012
DOI: 10.1038/nn.3183
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation of Syd-1 with Neurexin synchronizes pre- with postsynaptic assembly

Abstract: Understanding the process of synapse assembly in molecular and cell-biological detail is a prerequisite for understanding neural circuit development and activity-mediated remodeling, and thus is important for unraveling learning and memory processes (structural plasticity) [1][2][3] . Functional chemical synapses are characterized by two apposed compartments that must be coestablished with high spatiotemporal precision: the presynaptic active zone, where regulated and rapid fusion of neurotransmitter-filled sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
145
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(157 citation statements)
references
References 47 publications
5
145
0
Order By: Relevance
“…Mutants of syd-1 and liprin-⍺ have irregular T-bars, which may be small, misshapen, ectopic, or enlarged multi-T-bars, consistent with a role in regulating CAZ assembly (Kaufmann et al 2002;Owald et al 2010). Syd-1 clusters Liprin-⍺ at the CAZ along with the transsynaptic adhesion protein Neurexin (Nrx), which is important for transsynaptic signaling for PSD organization and apposition (Owald et al , 2012. A Drosophila ortholog of Piccolo, a core CAZ protein previously thought to exist only in vertebrates, was recently identified and named fife.…”
Section: The Active Zone Cytomatrixmentioning
confidence: 89%
See 3 more Smart Citations
“…Mutants of syd-1 and liprin-⍺ have irregular T-bars, which may be small, misshapen, ectopic, or enlarged multi-T-bars, consistent with a role in regulating CAZ assembly (Kaufmann et al 2002;Owald et al 2010). Syd-1 clusters Liprin-⍺ at the CAZ along with the transsynaptic adhesion protein Neurexin (Nrx), which is important for transsynaptic signaling for PSD organization and apposition (Owald et al , 2012. A Drosophila ortholog of Piccolo, a core CAZ protein previously thought to exist only in vertebrates, was recently identified and named fife.…”
Section: The Active Zone Cytomatrixmentioning
confidence: 89%
“…Two groups have reported that loss of nrx-1 results in an increase in A-type receptors, suggesting that Nrx-1 normally inhibits A-type receptor clustering (Li et al 2007;Chen et al 2010). In contrast, live imaging of GluR incorporation revealed that mutants for nrx-1, as well as interacting partners nlg-1 and syd-1, are deficient in early GluRIIA incorporation (Owald et al 2012). While newly formed GluR clusters are typically rich in GluRIIA, these mutants have new clusters that are rich in GluRIIB.…”
Section: Ionotropic Glutamate Receptors At the Nmjmentioning
confidence: 99%
See 2 more Smart Citations
“…In this analysis, the top GO annotation cluster corresponds to neuron/cell projection morphogenesis or development ( Table 2). msp-300 (Elhanany- Tamir et al 2012;Volk 2013;Morel et al 2014), syd-1 (Owald et al 2010(Owald et al , 2012, nrx-1 (Li et al 2007;Zeng et al 2007;Owald et al 2012), and futsch (Roos et al 2000;Zhang et al 2001) were among the top hits, while hiw (Wan et al 2000;McCabe et al 2004;Wu et al 2005;Collins et al 2006), dlg1 (Lahey et al 1994;Budnik et al 1996;Guan et al 1996;Tejedor et al 1997;Thomas et al 1997), and α-spec (Featherstone et al 2001;Pielage et al 2005Pielage et al , 2006 were also found to associate with Syp ( Fig. 4A; Table 1; Supplemental Table 1; Supplemental Fig.…”
Section: Syp Protein Associates Specifically With Key Synaptic Transcmentioning
confidence: 99%